Person-job fit and work-life balance of female nurses with cultural competence as a mediator: evidence from Nigeria - Akanni Abimbola A.; Oduaran Choja A. (Sciendo, 2022)
This study investigated the mediating effect of cultural competence in the relationship between person-job (P-J) fit and work-life balance among female nurses.